Gains from stock market timing - Chua, Jess H.; Woodward, Richard S.; Saunders, Anthony (New York : The Salomon Brothers Center for the Study of Financial Institutions, 1986)
This book aimed at achieving the highest possible reward for a given level of risk.
Includes bibliographical references: p. 72-73.
oo 16/04/2019
Loans